Ablation-resistant hybrid resin containing covalent-ionic bicontinuous network as well as preparation method and application of ablation-resistant hybrid resin
By introducing a covalent-ionic dual continuous network structure into organic-inorganic hybrid resins, the interface defects existing in the high-temperature oxidation resistance process are solved, and the high-temperature oxidation resistance and ablation resistance are significantly improved, which is suitable for thermal protection materials.
Patent Information
- Application Number
- CN202510078953.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing organic-inorganic hybrid resins have interface defects in the high-temperature antioxidant process, making it difficult to have high heterogeneous element content and excellent two-phase interfaces, and it is difficult to exert the coordinated enhancement mechanism between inorganic antioxidant ceramics and high-strength graphitized carbon layers at high temperatures.
By introducing ablation-resistant hybrid resin with a covalent-ionic dual continuous network structure, inorganic ion oligomers are prepared using raw materials such as salts of metal cations, acid ion donors and capping agents, and reacting them with monomer compounds and modified phenolic resins to form a hybrid resin with excellent ablation resistance.
It has achieved the elimination of interface defects at high temperatures, significantly improved the material's high-temperature oxidation resistance and ablation resistance, and has a covalent-ionic dual-continuous network with a continuous structure from macroscopic to microscopic scale, which is suitable for the field of thermal protection materials.
Smart Images

Figure CN119875137A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of heat protection materials, and in particular relates to an ablation-resistant hybrid resin containing a covalent-ionic double continuous network, and a preparation method and application thereof. Background Art
[0002] Resin-based ablative thermal protection materials have high thermal protection efficiency and reliable operation. They are currently the most widely used type of thermal protection materials and structures, and phenolic resin-based composite materials play a very important role in aircraft thermal protection composite materials. Phenolic resin is often used as the matrix of anti-ablative composite coatings due to its simple molding process, good heat resistance, high mechanical strength, and outstanding instantaneous high-temperature ablation resistance. The PhenCarb series of lightweight carbonized ablative materials prepared by NASA in the United States with phenolic resin as the matrix have low surface ablation rate and thick carbon layer after ablation. The phenolic impregnated carbon ablative material (PICA) prepared by the AMES Center in the United States with phenolic resin as the matrix has been successfully used in the thermal protection system of the Stardust return capsule.
[0003] However, the new generation of high-speed aircraft needs to fly for a long time in an aerobic environment. Traditional phenolic resins are difficult to meet their thermal protection requirements due to low residual carbon rate and lack of oxidation resistance. It is urgent to develop new high-performance high-temperature antioxidant phenolic resins. The organic-inorganic hybrid structure formed by introducing inorganic components into the resin structure can effectively improve the long-term antioxidant performance of the resin. Traditional organic-inorganic hybrid resins are usually prepared by the following three methods: (1) adding inorganic fillers; (2) bonding with inorganic ions through ionic bonds or coordination bonds; (3) copolymerization and grafting modification with inorganic element monomers represented by silane through covalent bonds. For organic-inorganic hybrid resins, reducing the size of inorganic units can effectively enhance the interaction between the two phases and reduce or eliminate the boundary between the organic and inorganic phases in the hybrid material, effectively improving the comprehensive performance of the hybrid resin. However, the molecular structure design of existing organic-inorganic hybrid resins has problems such as limited types of inorganic elements introduced, difficulty in combining high heterogeneous element content with excellent two-phase interface, and difficulty in exerting the synergistic reinforcement mechanism of inorganic antioxidant ceramics and high-strength graphitized carbon layers during high-temperature anti-oxidation.
[0004] Based on the problems existing in the existing organic-inorganic hybrid resins, there is an urgent need to design an organic-inorganic hybrid resin that can eliminate interface defects and also exhibit excellent heat resistance and ablation resistance during high-temperature anti-oxidation processes. Summary of the invention
[0005] In view of the problems of the prior art, the present invention provides an ablation-resistant hybrid resin containing a covalent-ionic dual continuous network, and a preparation method and use thereof.
[0006] A hybrid resin with ablation resistance is prepared by curing the following raw materials in parts by weight:
[0007] 10-30 parts of salt containing metal cations,
[0008] 4-10 parts of acid radical donor,
[0009] Capping agent 150-900 parts,
[0010] 5-30 parts of monomer compound,
[0011] 2-120 parts of modified phenolic resin;
[0012] The monomer compound is a compound having a carboxyl group at one end and a group capable of reacting with a phenolic resin at the other end.
[0013] Preferably, the group that can react with the phenolic resin is selected from at least one of an epoxy group, a maleimide group, a cyanate group, an isocyanate group, an amino group, a carboxyl group, a hydroxyl group, an aldehyde group, a thiol group, and a boric acid group.
[0014] Preferably, it is made by curing the following raw materials in parts by weight:
[0015] 12 parts of salt containing metal cations,
[0016] 8 parts of acid radical donor,
[0017] 166 parts of end-capping agent,
[0018] 7 parts of monomer compound,
[0019] 30 parts of modified phenolic resin.
[0020] Preferably, the metal cation is selected from at least one of calcium ion, copper ion, manganese ion, zirconium ion, hafnium ion, magnesium ion and iron ion; the anion of the salt containing the metal cation is selected from at least one of chloride ion, carbonate ion, sulfate ion, nitrate ion and phosphate ion;
[0021] Preferably, the monomer compound is selected from at least one of phenylboronic acid compounds, hydroxybenzoic acid compounds, hydroxyphenylacetic acid compounds, hydroxyphenylpropionic acid compounds, thioglycolic acid compounds, and thiobenzoic acid compounds.
[0022] Preferably, the modified phenolic resin is selected from any one of boron phenolic resin, epoxy modified phenolic resin, polyamide modified phenolic resin, silicone modified phenolic resin, dicyandiamide modified phenolic resin, polyvinyl acetal modified phenolic resin and diphenyl ether formaldehyde resin.
[0023] Preferably, the acid ion donor is selected from at least one of phosphoric acid, CO2, sulfuric acid and nitric acid; and / or the capping agent is selected from triethylamine.
[0024] The present invention also provides a method for preparing the hybrid resin having ablation resistance, comprising the following steps: Step 1, preparing an inorganic ion oligomer by using a salt containing a metal cation, a capping agent, and an acid radical ion donor;
[0025] Step 2, reacting the monomer compound with the inorganic ion oligomer obtained in step 1 to obtain an organic functionalized inorganic ion oligomer;
[0026] Step 3: reacting the modified phenolic resin with the organic functionalized inorganic ion oligomer obtained in step 2 to obtain a hybrid resin with ablation resistance.
[0027] Preferably, in step 1, the preparation method of the inorganic ion oligomer is as follows: step 1.1, reacting a salt containing a metal cation with a complexing agent to obtain a solution A;
[0028] Step 1.2, reacting the acid ion donor with the complexing agent to obtain solution B;
[0029] Step 1.3, after the solution A reacts with the solution B, a dispersion 1 of inorganic ion oligomers is obtained;
[0030] Step 1.4, the inorganic ion oligomer dispersion 1 is centrifuged to obtain an inorganic ion oligomer gel, which is then washed and dispersed to obtain;
[0031] And / or, in step 2, the preparation method of the organic functionalized inorganic ion oligomer is:
[0032] Step 2.1, reacting the monomer compound with the inorganic ion oligomer to obtain a dispersion 1 of the organic functionalized inorganic ion oligomer;
[0033] Step 2.2, centrifuging the dispersion 1 of the organic functionalized inorganic ion oligomer to obtain an organic functionalized inorganic ion oligomer gel, and washing and dispersing the gel to obtain;
[0034] And / or, in step 3, the preparation method of the hybrid resin is: reacting the organic functionalized inorganic ion oligomer with the modified phenolic resin, obtaining a hybrid resin gel by centrifugation, washing and drying to obtain a hybrid resin powder, and then curing to obtain the hybrid resin powder.
[0035] Preferably, in steps 1.1 and 1.2, the solvent of the reaction is anhydrous ethanol; in step 1.3, the reaction time is 6-24h; in step 1.4, the centrifugal speed is 5000-12000rpm, the centrifugal time is 1-10min, the reagent used for washing is ethanol, and the dispersant is anhydrous ethanol.
[0036] Preferably, in step 2.1, the solvent of the monomer compound is anhydrous methanol, and the reaction time is 6-24h; in step 2.2, the centrifugal speed is 5000-12000rpm, the centrifugal time is 1-10min, the reagent used for washing is ethanol, and the dispersant is anhydrous ethanol.
[0037] Preferably, in step 3, the reaction temperature is 70-90°C, the reaction time is 4-8h under inert atmosphere; the centrifugal speed is 5000-12000rpm, and the centrifugal time is 1-10min; the reagent used for washing is ethanol; the drying condition is 70-90°C, -0.08--0.1MPa; the curing condition is 100-120°C for 20-40min, and the pressure is maintained at 25-35MPa; the temperature is increased from 100-120°C to 130-150°C, the heating rate is 5-20°C / min; the temperature is kept at 130-150°C for 20-40min. 20-40min, maintain the pressure at 25-35MPa; heat from 130-150℃ to 170-190℃, heating rate 5-20℃ / min, maintain the pressure at 25-35MPa; keep at 170-190℃ for 1-3h, maintain the pressure at 25-35MPa; heat from 170-190℃ to 190-210℃, heating rate 5-20℃ / min, maintain the pressure at 25-35MPa; keep at 190-210℃ for 0.5-1.5h, maintain the pressure at 25-35MPa; finally maintain the pressure at 25-35MPa.
[0038] The present invention also provides the use of the hybrid resin having ablation resistance in the preparation and / or as ablation resistant material.
[0039] The molecular precision described in the present invention means that the molecular formula of the functionalized inorganic ion oligomer is clear.
[0040] The present invention introduces inorganic ion oligomers functionalized with organic groups with molecular precision into boron phenolic resin, and for the first time realizes the simultaneous initiation of crosslinking and polymerization of thermosetting network and inorganic ion network in hybrid resin, and obtains a covalent-ion double continuous network with a continuous structure from macroscopic to microscopic scale. The construction method of the covalent-ion double continuous network between the functionalized inorganic ion oligomer and phenolic resin makes it possible to precisely control other organic-inorganic thermosetting hybrid resins. At the same time, the hybrid resin of the present invention has excellent high-temperature antioxidant ability and ablation resistance, and has broad application prospects in the field of thermal protection materials.
[0041] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0042] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Molecular structure characterization of functionalized inorganic ion oligomers. (a) Schematic diagram of the synthesis and structure of 3-BAPO; (b) IR spectrum of 3-BAPO; (c) Elemental analysis of 3-BAPO using ICP-OES plasma spectrometer.
[0044] Figure 2 Characterization of supramolecular interaction between functionalized inorganic ion oligomers and boron phenolic resin in 3-BRPO. (a) Infrared spectrum test diagram; (b) Raman spectrum diagram; (ce) X-ray photoelectron spectroscopy (XPS).
[0045] Figure 3 is the relative content of inorganic elements in 3-BRPO hybrid resin powder (before curing).
[0046] Figure 4 Characterization of the cross-linked network structure of 3-BRPO hybrid resin before and after curing.
[0047] Figure 5 This is the optical morphology of 3-BRPO hybrid resin.
[0048] Figure 6 It is a dual-continuous phase structure of 3-BRPO hybrid resin.
[0049] Figure 7 Small angle X-ray scattering (SAXS) characterization of 3-BRPO hybrid resin.
[0050] Figure 8 Thermogravimeter was used to characterize the heat resistance of hybrid resin.
[0051] Fig. 9 The static ablation performance of the hybrid resin is characterized by a tube furnace. (a) Photos of 3-BPROa before and after static ablation in a tube furnace; (b) Photos of BPR before and after static ablation in a tube furnace; (c) XRD of the carbonized ceramic product after static ablation of 3-BRPOa.
[0052] Fig.10 The dynamic ablation performance of 3-BPRO hybrid resin in oxygen-rich atmosphere was characterized for plasma ablation machine.
[0053] Fig.11 Nanoindentation was used to characterize the mechanical properties of 3-BPRO hybrid resin. DETAILED DESCRIPTION
[0054] In the following examples and experimental examples, reagents and raw materials not specifically described are all commercially available products.
[0055] Example 1 Preparation of 3-carboxyphenylboronic acid functionalized calcium phosphate inorganic ion oligomer boron phenolic resin (3-BRPO)
[0056] 1. Preparation of Calcium Phosphate Inorganic Ion Oligomers (CPO)
[0057] Take 80mmol of calcium chloride dihydrate and dissolve it in 1L of anhydrous ethanol, add 800mmol of triethylamine and continue stirring for 10min to obtain solution A. Disperse 80mmol of phosphoric acid and 800mmol of triethylamine in 1L of anhydrous ethanol to obtain solution B. Add solution B dropwise to solution A, and continue to react for 24h after the addition is complete to obtain CPO ethanol dispersion 1. High-speed centrifugation (10000rpm, 2min) is used to obtain CPO gel. The CPO gel is washed with ethanol several times to remove the residual triethylamine, and the CPO gel is redispersed in 1L of anhydrous ethanol to obtain CPO ethanol dispersion 2.
[0058] 2. Preparation of 3-carboxyphenylboronic acid functionalized calcium phosphate inorganic ion oligomer (3-BAPO)
[0059] 42 mmol of 3-carboxyphenylboronic acid (3-CPBA) was weighed and dissolved in 800 mL of anhydrous methanol. The CPO ethanol dispersion 2 obtained above was added dropwise into the methanol solution of 3-CPBA. After the addition was completed, the reaction was continued for 24 hours to obtain 3-BAPO ethanol dispersion 1. 3-BAPO gel was obtained by high-speed centrifugation (10000 rpm, 2 min). The 3-BAPO gel was washed with ethanol for multiple times to remove residual 3-CPBA. The above 3-BAPO gel was redispersed in 1 L of anhydrous ethanol to obtain 3-BAPO ethanol dispersion 2.
[0060] 3. Preparation of 3-BAPO / boron phenolic resin hybrid material (3-BRPO)
[0061] Boron phenolic resin (THC-400 from Shaanxi Taihang Fire Resistant Company) and 200g ethanol were added to a flask, stirred at room temperature until the boron phenolic resin (BPR) was completely dissolved, then heated to 80°C, and 3-BAPO ethanol dispersion 2 was added dropwise through a constant pressure dropping funnel under argon conditions. After the addition was completed, the reaction was continued at 80°C for 6h. After the reaction was completed, 3-BRPO gel was obtained by high-speed centrifugation (10000rpm, 2min). The 3-BRPO gel was washed with ethanol for multiple times to remove the residual BPR, and then the solvent was removed in a vacuum oven (80°C, -0.1MPa) to obtain 3-BRPO powder. Curing process: 110℃ for 30min, pressure 30MPa; heating from 110℃ to 140℃, heating rate 5℃ / min; 140℃ for 30min, pressure 30MPa; heating from 140℃ to 180℃, heating rate 5℃ / min, pressure 30MPa; 180℃ for 2h, pressure 30MPa; heating from 180℃ to 200℃, heating rate 5℃ / min, pressure 30MPa; 200℃ for 1h, pressure 30MPa; finally, pressure 30MPa, cooling to room temperature naturally, and the obtained product is obtained. The amount of boron phenolic resin (BPR) is shown in Table 1, and 3-BRPOa, 3-BRPOb, and 3-BRPOc are prepared respectively.
[0062] Table 1
[0063] name BPR Anhydrous ethanol 3-BRPOa 60g 200g 3-BRPOb 30g 200g 3-BRPOc 5g 200g
[0064] The following is the preparation method of the control sample.
[0065] Comparative Example 1
[0066] 1. Calcium phosphate (Ca3(PO4)2)
[0067] The sample is calcium phosphate inorganic ion oligomer (CPO), which is prepared according to step 1 of Example 1.
[0068] 2. BPR
[0069] The sample is boron phenolic resin.
[0070] 3. 3-BAPO
[0071] The sample was prepared according to step 2 of Example 1.
[0072] 4. 3-CPBA
[0073] The sample is 3-carboxyphenylboronic acid.
[0074] The technical solution of the present invention is further illustrated by experiments below.
[0075] Experimental Example 1: Molecular structure characterization of functionalized inorganic ion oligomer (3-BAPO)
[0076] The 3-BAPO, 3-CPBA and Ca3(PO4)2 in this experimental example were prepared according to the method of Comparative Example 1.
[0077] 1. Experimental Methods
[0078] The molecular structure of 3-BAPO molecules was characterized by infrared spectroscopy and ICP-OES plasma spectrometer.
[0079] 2. Experimental Results
[0080] like Figure 1 (a) shows the synthesis and structural schematic diagram of 3-BAPO. Calcium phosphate inorganic ion oligomer (CPO) and 3-carboxyphenylboronic acid (3-CPBA) are reacted to obtain 3-carboxyphenylboronic acid functionalized calcium phosphate inorganic ion oligomer (3-BAPO). Figure 1 (b) In the infrared spectrum, the 3-CPBA line can be found at 1686 cm -1 The C=O peak was observed at 1545 cm-1. As the acid-base neutralization reaction of 3-CPBA and CPO proceeded, this peak red-shifted to 1545 cm-1. -1 The changes in the FTIR spectrum confirmed that an ionic bond was formed between the carboxyl group in 3-CPBA and the phosphoric acid in CPO, indicating that there was a strong chemical interaction between the two. Figure 1 As shown in (c), ICP-OES confirmed that the average Ca / B and P / B molar ratios were approximately 5:1 and 3:1, respectively, supporting the molecular formula of 3-BAPO as 3-CPBA3Ca3PO4(Ca3(PO4)2)4.
[0081] Experimental Example 2: Characterization of supramolecular interactions between functionalized inorganic ion oligomers and boron phenolic resin in 3-BRPO
[0082] In this experimental example, 3-BRPO b, BPR, 3-BAPO, 3-CPBA, and Ca3(PO4)2 were prepared according to the methods in Example 1 and Control Example 1.
[0083] 1. Experimental Methods
[0084] The supramolecular interaction between functionalized inorganic ion oligomers and boron phenolic resin in 3-BRPO hybrid resin powder (before curing) was characterized by infrared spectroscopy, Raman spectroscopy and X-ray photoelectron spectroscopy (XPS).
[0085] 2. Experimental Results
[0086] Figure 2 In infrared spectrum, 1380cm -1654cm -1 The BO peak intensity at 1200 cm-1 is significantly reduced, indicating that 3-BAPO coordinates with B and O in BPR. -1 The Ph-OH peak at 47° moves toward the high wavenumber direction, indicating that the hydroxyl groups in BPR form hydrogen bonds with the phosphate groups in the calcium phosphate oligomers.
[0087] Figure 2 b The PO peak in the Raman spectrum broadens and shifts, indicating that the hydroxyl groups in BPR form hydrogen bonds with calcium phosphate.
[0088] Figure 2 In the cXPSCa2p fine spectrum, due to Ca 2+ The binding energy between the functionalized inorganic ion oligomer and the carboxylate group is higher, and the Ca2p peak moves toward the high binding energy direction after 3-carboxyphenylboronic acid functionalization, indicating that the organic functionalization of calcium phosphate oligomers was successfully achieved through acid-base neutralization reaction. In addition, the Ca2p peak of the hybrid resin powder further moves toward the high binding energy direction, and the orbital electron density of calcium changes, indicating that supramolecular interactions occur between the functionalized inorganic ion oligomer and the boron phenolic resin, increasing the Ca 2+ Binding energy with the surrounding chemical environment.
[0089] Figure 2 In the dXPS O1s fine spectrum, the phosphate peak in the hybrid resin powder and the peak of the boron phenolic resin were significantly shifted compared with 3-BAPO and BPR, moving towards the high binding energy and low binding energy directions, respectively, indicating that the oxygen-containing structures in the two structures have produced supramolecular interactions with each other.
[0090] Figure 2 In the eXPS B1s fine spectrum, characteristic peaks of boron-oxygen coordination can be observed in the hybrid resin powder. 3-BAPO and BPR contain both B and O elements, so the above peaks indicate that the B and O elements of the inorganic and organic structures in the hybrid resin are coordinated with each other.
[0091] Experimental Example 3: Characterization of element content of 3-BRPO hybrid resin
[0092] In this experimental example, 3-BRPO a, 3-BRPO b, and 3-BRPO c were prepared according to the method in Example 1.
[0093] 1. Experimental Methods
[0094] The relative contents of inorganic elements in the hybrid resin powder (before curing) were characterized by ICP-OES plasma spectrometer.
[0095] 2. Experimental Results
[0096] like Figure 3As shown, the results show that by adjusting the concentration of the boron phenolic resin ethanol solution, a hybrid resin with a total inorganic element content between 13.5 and 25.9 wt.% was successfully prepared.
[0097] Experimental Example 4: Characterization of the cross-linked network structure of 3-BRPO hybrid resin before and after curing
[0098] In this experimental example, 3-BRPO b (Cured) is the 3-BRPO hybrid resin after curing, and 3-BRPO b is the 3-BRPO hybrid resin before curing; BPR (Cured) is the boron phenolic resin after curing, and BPR is the boron phenolic resin before curing, all of which are prepared according to the methods in Example 1 and Comparative Example 1.
[0099] 1. Experimental Methods
[0100] X-ray diffractometer (XRD) was used to characterize whether the high pressure gradient temperature process could simultaneously stimulate the curing of boron phenolic resin and the inorganic ion polymerization of amorphous calcium phosphate network in the hybrid resin.
[0101] 2. Experimental Results
[0102] like Figure 4 As shown, the boron phenolic resin has a passivated amorphous diffraction peak at about 20°, corresponding to the amorphous resin network. This peak moves toward the low angle direction as the curing progresses, indicating that the cross-linked network formed after the resin is cured is more disordered. In the XRD spectrum of the hybrid resin 3-BRPOb, amorphous diffraction peaks corresponding to the amorphous resin network (~20°) and the amorphous calcium phosphate network (~30°) can be observed simultaneously. Consistent with the results observed for the above-mentioned boron phenolic resin, the amorphous diffraction peak of the resin network in the hybrid resin moves toward the low angle direction after curing, indicating that the cross-linking of the organic part in the hybrid resin is successfully activated. The amorphous diffraction peak corresponding to the amorphous calcium phosphate network moves toward the high angle direction after curing, indicating that the Ca-O coordination number in the system increases, proving that the inorganic ion part in the hybrid resin can form an amorphous calcium phosphate network through inorganic ion polymerization through the high pressure gradient heating process.
[0103] In summary, XRD proved that the high pressure gradient temperature rising process can simultaneously stimulate the curing of boron phenolic resin and the inorganic ion polymerization of amorphous calcium phosphate network in the hybrid resin.
[0104] Experimental Example 5: Characterization of organic-inorganic bicontinuous network after curing of 3-BRPO hybrid resin
[0105] In this experimental example, 3-BRPO a, 3-BRPO b, and 3-BRPO c were prepared according to the method in Example 1.
[0106] 1. Experimental Methods
[0107] The bicontinuous network of the hybrid resin after curing was characterized by optical morphology, high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and small-angle X-ray scattering (SAXS).
[0108] 2. Experimental Results
[0109] like Figure 5 As shown, all hybrid resins do not scatter visible light and exhibit a uniform and transparent macroscopic morphology, indicating that the obtained resin castings are all nanoscale bicontinuous materials.
[0110] like Figure 6 As shown, a continuous calcium-containing microphase separation structure (light-colored area) can be clearly observed, and this structure is interspersed with the uniform permeable phase of BPR (dark-colored area) to form a dual-continuous phase structure.
[0111] like Figure 7 As shown, it can be observed that the single scattering peak centered on the vector q = 0.038A-1 shows the typical scattering pattern of the bicontinuous structure. The curve is further fitted with the Teubner-Strey model to obtain a dTS of 16.3 nm and an amphiphilic factor fa = -0.42, proving the existence of a molecular-scale bicontinuous network in 3-BRPO.
[0112] The Teubner-Strey model comes from the literature: Bobrin, VA, Yao, Y., Shi, X. et al. Nano-tomacro-scale control of 3D printed materials via polymerization induced microphase separation. Nat Commun 13, 3577 (2022).
[0113] Experimental Example 6: Characterization of heat resistance of 3-BRPO hybrid resin
[0114] In this experimental example, 3-BRPO a, 3-BRPO b, 3-BRPO c and BPR were prepared according to the methods in Example 1 and Comparative Example 1.
[0115] 1. Experimental Methods
[0116] The heat resistance of the hybrid resin was characterized by thermogravimeter (TG).
[0117] 2. Experimental Results
[0118] like Figure 8As shown, the constructed organic-inorganic bicontinuous network can significantly improve the residual weight of the material at 1200°C in an air atmosphere, and to a certain extent slow down or inhibit the degradation of the resin at 800-1200°C. The constructed organic-inorganic bicontinuous network can significantly improve the residual weight of the material at 1200°C in an air atmosphere, and to a certain extent slow down or inhibit the degradation of the resin at 800-1200°C. Therefore, the hybrid resin exhibits good heat resistance.
[0119] Experimental Example 7: Static Ablation Performance of 3-BRPO Hybrid Resin
[0120] In this experimental example, 3-BRPO a and BPR were prepared according to the methods in Example 1 and Comparative Example 1.
[0121] 1. Experimental Methods
[0122] The static ablation performance of the hybrid resin was characterized by a tubular furnace (1200°C for 30 min, heating rate 5°C / min).
[0123] 2. Experimental Results
[0124] Fig. 9 As can be seen from a and b, the hybrid resin generates a dense ceramic layer through high-temperature static ablation in an oxidizing atmosphere, and the structure remains intact, while the glassy carbon obtained from pure phenolic resin is completely oxidized. Fig. 9 c The results show that the carbonized ceramic products of the hybrid resin after static ablation are mainly composed of amorphous carbon, calcium phosphate, calcium carbide and calcium oxide.
[0125] Experimental Example 8: Plasma Dynamic Ablation Performance of 3-BRPO Hybrid Resin
[0126] In this experimental example, 3-BRPO b and BPR were prepared according to the methods in Example 1 and Comparative Example 1.
[0127] 1. Experimental Methods
[0128] The dynamic ablation performance of the hybrid resin in an oxygen-rich atmosphere was characterized by a plasma ablation machine (0.5 MW / m2; nitrogen flow / oxygen flow = 1; ablation time 60 s).
[0129] 2. Experimental Results
[0130] Fig.10 It can be seen that the hybrid resin generates a dense ceramic layer when ablated on the surface in an oxygen-rich atmosphere, while the glassy carbon obtained from the pure phenolic resin is completely exposed to the flame. The covalent-ionic bicontinuous hybrid resin exhibits excellent ablation resistance in an oxygen-rich environment, and the mass ablation rate is 24% lower than that of the boron phenolic resin (BPR group). Therefore, it is proved that the covalent-ionic bicontinuous network constructed by the present invention can effectively improve the ablation resistance of the resin material.
[0131] Experimental Example 9: Mechanical Properties of 3-BRPO Hybrid Resins
[0132] In this experimental example, 3-BRPOb and BPR were prepared according to the methods in Example 1 and Control Example 1.
[0133] 1. Experimental Methods
[0134] The mechanical properties of 3-BRPO hybrid resin were characterized by nanoindentation.
[0135] 2. Experimental Results
[0136] Fig.11 It can be seen that the modulus of the 3-BRPO hybrid resin is increased by 52.4% compared with the pure BPR sample, indicating that the successful construction of the organic-inorganic dual continuous network in the hybrid resin has greatly improved the modulus of the material and can effectively improve the mechanical properties of the resin material.
[0137] In summary, the hybrid resin prepared by the present invention has a covalent-ionic double continuous network with a continuous structure from macroscopic to microscopic scales, and has excellent high-temperature antioxidant ability, ablation resistance and mechanical properties, and has broad application prospects in the field of thermal protection materials.
Claims
1. A hybrid resin having ablation resistance, characterized in that: It is made by curing the following raw materials by weight: 10-30 parts of salt containing metal cations, 4-10 parts of acid radical donor, Capping agent 150-900 parts, 5-30 parts of monomer compound, 2-120 parts of modified phenolic resin; The monomer compound is a compound having a carboxyl group at one end and a group capable of reacting with a phenolic resin at the other end.
2. The hybrid resin having ablation resistance according to claim 1, characterized in that: The group capable of reacting with the phenolic resin is selected from at least one of an epoxy group, a maleimide group, a cyanate group, an isocyanate group, an amino group, a carboxyl group, a hydroxyl group, an aldehyde group, a thiol group, and a boric acid group.
3. The hybrid resin having ablation resistance according to claim 1, characterized in that: It is made by curing the following raw materials by weight: 12 parts of salt containing metal cations, 8 parts of acid radical donor, 166 parts of end-capping agent, 7 parts of monomer compound, 30 parts of modified phenolic resin.
4. The hybrid resin having ablation resistance according to any one of claims 1 to 3, characterized in that: The metal cation is selected from at least one of calcium ion, copper ion, manganese ion, zirconium ion, hafnium ion, magnesium ion and iron ion; the anion of the salt containing metal cation is selected from at least one of chloride ion, carbonate ion, sulfate ion, nitrate ion and phosphate ion.
5. The hybrid resin having ablation resistance according to any one of claims 1 to 3, characterized in that: The monomer compound is selected from at least one of phenylboronic acid compounds, hydroxybenzoic acid compounds, hydroxyphenylacetic acid compounds, hydroxyphenylpropionic acid compounds, thioglycolic acid compounds, and thiobenzoic acid compounds.
6. The hybrid resin having ablation resistance according to any one of claims 1 to 3, characterized in that: The modified phenolic resin is selected from any one of boron phenolic resin, epoxy modified phenolic resin, polyamide modified phenolic resin, silicone modified phenolic resin, dicyandiamide modified phenolic resin, polyvinyl acetal modified phenolic resin and diphenyl ether formaldehyde resin.
7. The hybrid resin having ablation resistance according to any one of claims 1 to 3, characterized in that: The acid ion donor is selected from at least one of phosphoric acid, CO2, sulfuric acid and nitric acid; and / or the end-capping agent is selected from triethylamine.
8. The method for preparing a hybrid resin having ablation resistance according to any one of claims 1 to 7, characterized in that: The steps include: Step 1, preparing an inorganic ion oligomer using a salt containing a metal cation, a capping agent, and an acid ion donor; Step 2, reacting the monomer compound with the inorganic ion oligomer obtained in step 1 to obtain an organic functionalized inorganic ion oligomer; Step 3: reacting the modified phenolic resin with the organic functionalized inorganic ion oligomer obtained in step 2 to obtain a hybrid resin with ablation resistance.
9. The preparation method according to claim 8, characterized in that: In step 1, the preparation method of the inorganic ion oligomer is: Step 1.1, reacting a salt containing a metal cation with a complexing agent to obtain a solution A; Step 1.2, reacting the acid ion donor with the complexing agent to obtain solution B; Step 1.3, after the solution A reacts with the solution B, a dispersion 1 of inorganic ion oligomers is obtained; Step 1.4, the inorganic ion oligomer dispersion 1 is centrifuged to obtain an inorganic ion oligomer gel, which is then washed and dispersed to obtain; And / or, in step 2, the preparation method of the organic functionalized inorganic ion oligomer is: Step 2.1, reacting the monomer compound with the inorganic ion oligomer to obtain a dispersion 1 of the organic functionalized inorganic ion oligomer; Step 2.2, centrifuging the dispersion 1 of the organic functionalized inorganic ion oligomer to obtain an organic functionalized inorganic ion oligomer gel, and washing and dispersing the gel to obtain; And / or, in step 3, the preparation method of the hybrid resin is: reacting the organic functionalized inorganic ion oligomer with the modified phenolic resin, obtaining a hybrid resin gel by centrifugation, washing and drying to obtain a hybrid resin powder, and then curing to obtain the hybrid resin powder.
10. Use of the hybrid resin with ablation resistance according to any one of claims 1 to 7 in the preparation and / or as ablation resistant material.
Citation Information
Patent Citations
Preparation method of organic-inorganic hybrid biomass phenolic resin ablation-resistant material
CN113621215A
Poly (dimethyl diphenyl imide) siloxane / phenolic aldehyde-based dual-network hybrid resin as well as preparation method and application of poly (dimethyl diphenyl imide) siloxane / phenolic aldehyde-based dual-network hybrid resin
CN118994575A
Organic / inorganic hybrid composition with electrostatic discharge protection property
US20090236132A1
Modified phenolic-resin fiber and method for fabricating same and use of same, and composite material made of said modified phenolic-resin fiber and used for electrode
WO2018033161A1
Cited By
Amine modified oligomer cross-linked epoxy resin material, preparation method and application
CN121673643A